Impact of a dementia-specific program of equine-assisted activities: providers' perspectives. (30th May 2019) - Fields, Beth; Wood, Wendy; Lassell, Rebecca
Abstract : Purpose: Establishing acceptability of complex interventions to stakeholders is vital in early scientific development. The purpose of this paper is to ascertain the acceptability of a program of equine-assisted activities (EAAP) for people with dementia by elucidating programmatic practices needed to enhance their safety and quality of life (QoL) from the perspectives of service providers. Design/methodology/approach: Semi-structured interviews with five providers were analyzed using a basic qualitative approach. Findings: Providers perceived the EAAP as acceptable and revealed potential mechanisms of change supporting well-being, including aspects related to the physical and social environment and person with dementia. Linkages identified among the EAAP and its physical and social context support its complexity. Providers explicated program practices that promoted safety and QoL, such as implementing staff trainings and tailoring activities to each person's preferences and needs. These practices aligned with best dementia care approaches, underscoring that the EAAP is a promising complex intervention that merits further scientific development. Originality/value: This work is novel and adds to the literature by illuminating the role of a community-based, animal-assisted program for enhancing the QoL of older adults with dementia residing in institutional care facilities.